Mapping influential CLIL research in English language teaching: a bibliometric SWOT analysis - Lim Seong Pek; Fatin Syamilah Che Yob; Azie Azlina Azmi; Desmond Sandum; Gilbert C. Magulod Jr.; Choiril Anwar (International Journal of Evaluation and Research in Education (IJERE), 2026)
Content and language integrated learning (CLIL) has gained increasing attention in English language teaching (ELT); however, existing reviews often describe trends without critically examining both research impact and developmental challenges. This study addresses this gap by investigating the question: what directions and challenges characterize influential CLIL research in ELT? An integrative approach combining document-level bibliometric performance analysis and strengths, weaknesses, opportunities and threats (SWOT) analysis was employed. Using the Scopus database, the ten most-cited CLIL-related studies published between 2021 and 2025 were identified and systematically analyzed. The findings indicate that influential CLIL scholarship centers on pedagogical scaffolding, teacher cognition, learner motivation, and technology-enhanced learning environments. At the same time, recurring challenges include role ambiguity between content and language teachers, policy-practice misalignment in English-medium instruction (EMI) contexts, and limited longitudinal evidence of language outcomes. The study concludes that while CLIL research is increasingly shaped by digital innovation, sustainable implementation depends on pedagogical clarity, teacher preparation, and institutional alignment. By integrating bibliometric evidence with critical qualitative synthesis, this study provides theoretical and practical insights to guide future research, teacher education, and policy development aligned with sustainable development goal 4 (quality education).